2016
DOI: 10.1016/j.biopha.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Mutation R273H confers p53 a stimulating effect on the IGF-1R-AKT pathway via miR-30a suppression in breast cancer

Abstract: p53 is the most highly mutated tumor suppressor in human malignancies. A wide array of p53 mutations has been revealed to play pivotal roles during cancer progression, which abolish anti-tumor functions of wild type p53 but also elicit tumorigenic effects by activating a diverse subset of downstream molecules. R273H mutation of p53 has been closely implicated in human cancer. Here we report miR-30a as a novel downstream target of p53 R273H mutant, which binds to the promoter region to repress miR-30a expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…The impact of miR-30a and miR-31 on the initial and progress of BC seems to be deeply investigated than that in miR-22's studies. Other than the favorable biological functions such as inhibition of cell proliferation and migration [35,36] and activation of the IGF1R/PI3K/AKT pathway [37], miR-31 influences the BC apoptosis by protein kinase C epsilon [38,44] and regulates stem cell self-renewal and tumorigenesis by Wnt/β-catenin signaling [39], which is consistent with our enrichment analysis. Among the potential miRNA genes in the present study, we found that overexpression of miR-493 has been negatively correlated with monitoring the fidelity of chromosome segregation by mitotic arrest deficient-2 (MAD2), which predicts the efficacy of taxane chemotherapy [40].…”
Section: Discussionsupporting
confidence: 86%
“…The impact of miR-30a and miR-31 on the initial and progress of BC seems to be deeply investigated than that in miR-22's studies. Other than the favorable biological functions such as inhibition of cell proliferation and migration [35,36] and activation of the IGF1R/PI3K/AKT pathway [37], miR-31 influences the BC apoptosis by protein kinase C epsilon [38,44] and regulates stem cell self-renewal and tumorigenesis by Wnt/β-catenin signaling [39], which is consistent with our enrichment analysis. Among the potential miRNA genes in the present study, we found that overexpression of miR-493 has been negatively correlated with monitoring the fidelity of chromosome segregation by mitotic arrest deficient-2 (MAD2), which predicts the efficacy of taxane chemotherapy [40].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we have shown that targeting mutant TP53 downregulated IGF‐1R in osteosarcoma cells in vitro. It has been reported in breast cancers that mutant TP53 R273H released the inhibitory effect of miR‐30a on IGF‐1R expression, thus enhancing the activation of IGF‐1r/AKT signaling cascade . In addition to this, in hepatoma cells, mutant TP53 R249 was shown to enhance IGF‐IR signaling, which could be specifically prevented by an IGF‐IR antibody, alpha IR3, and lovastin in p53 negative cells …”
Section: Discussionmentioning
confidence: 79%
“…It has been reported in breast cancers that mutant TP53 R273H released the inhibitory effect of miR-30a on IGF-1R expression, thus enhancing the activation of IGF-1r/AKT signaling cascade. 38 In addition to this, in hepatoma cells, mutant TP53 R249 was shown to enhance IGF-IR signaling, which could be specifically prevented by an IGF-IR antibody, alpha IR3, and lovastin in p53 negative cells. 39 In this study, down-regulation of anti-apoptotic protein expression, including Bcl-2 and Survivin, after targeting mutant TP53 revealed the involvement of TP53 mutations in apoptotic signaling.…”
Section: Discussionmentioning
confidence: 89%
“…Aberrant dysregulation of phosphoinositide 3-kinase and Akt (PI3K/Akt) pathway plays a key role in many hallmarks of cancer and contributes to increase ROS levels through direct modulation of mitochondrial bioenergetics and activation of NOX, or through the generation of highly reactive metabolic by-products, as superoxide ions and H 2 O 2 [105][106][107]. Importantly, a number of studies demonstrated that mutant p53 stimulates PI3K/Akt activity, leading to a variety of oncogenic proprieties, such as cell survival, cell migration, metabolic re-wiring, and anoikis resistance [108][109][110].…”
Section: Regulation Of Akt/mtor Signaling By Mutant P53 Proteinsmentioning
confidence: 99%